Effects of sorghum hybrid and grain supplementation on the utilization of silage-based rations for growing cattle - Dalke, B.S.; Bolsen, K.K.; Sonon, R.N. Jr.; Holthaus, D.L.; Young, Matthew A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three whole-plant sorghum silages, each with or without 25% added rolled grain sorghum were fed to six medium-framed, ruminally cannulated steers in a 6 × 6 Latin square design. The grain sorghum silage rations (DeKalb 42Y) had the highest DM, OM, and ADF digestibilities; the late-season forage sorghum silage rations (DeKalb FS 25E), the lowest. Digestibility of NDF tended to be highest for the grain sorghum silage, but starch digestibilities were not affected by sorghum hybrid. Ruminal ammonia, acetate, propionate, butyrate, and total VFA concentrations were highest for the grain sorghum silage rations. Grain supplementation increased DM and OM digestibilities but had no effect on NDF, ADF, or starch digestibilities. Ruminal pH was decreased, whereas VFA concentrations were not affected by grain supplementation. The grain sorghum silage had the highest nutritive value, and the middle-season forage sorghum silage (DeKalb FS 5) was superior to the late-season forage sorghum. These results are consistent with several of our previous trials, which compared grain and forage sorghum silages for growing (backgrounding) cattle.
Keywords: Beef; Silage; Forage sorghum; Grain sorghum; Hybrid